Interleukin 17 deficiency and implications in cutaneous and systemic diseases - Elizabeth Z. Welch; Kathryn L. Anderson; Steven R. Feldman (Wolters Kluwer Medknow Publications, 2015)
Background: IL17-targeted therapeutics are being developed to treat psoriasis. IL17 is involved in the pathogenesis of many diseases, and the implications of IL17 blockade are not yet well characterized. Objective: To review the implications of IL17 deficiency to determine potential implications of IL17 blockade. Methods: PubMed was searched for articles related to; basic biology of IL17, in vitro and in vivo studies of IL17 deficiency, animal or human models of IL17 deficiency, and induced deficiency with anti-IL17 deficiency. Of 104 articles, 46 were included in this review. Results: Deficiencies in the IL17 pathway can result in both bacterial and fungal infections and increased tumor growth. IL17 deficiency states are associated with susceptibility to infections from Staphylococcus aureus, Mycobacterium tuberculosis and Candida albicans. IL17 deficiency attenuates rheumatoid arthritis, atopic dermatitis, hapten-induced contact hypersensitivity and irritable bowel disease and is protective in lung cancer. Limitations: Ultimately, clinical trials will determine the side effects of IL17 targeted therapeutics. Conclusion: The implications of the information found in this review demonstrate potential effects to consider when using IL17 targeted therapeutics in the treatment of psoriasis.